Establishment success of Brazil nut trees in smallholder Amazon forest restoration depends on site conditions and management - Brouwer, R.G.; Zuidema, Pieter A.; Chiriboga-Arroyo, Fidel; Guariguata, Manuel R.; Kettle, Christopher J.; Ehrenberg-Azcárate, F.; Quaedvlieg, J.; García Roca, M.R.; Corvera Gomringer, Ronald; Vargas Quispe, F.; Jansen, M. (Elsevier, 2021)
1. Forest landscape restoration (FLR) has gained momentum globally and guidance is needed to identify those species, sites and planting methods that increase restoration success. Incorporating native Non-Timber Forest Product (NTFP) species in FLR approaches provides an opportunity to simultaneously deliver ecological and economic benefits. The Brazil nut tree is one of the most valuable Amazonian NTFP species and could fulfil a cornerstone role in Amazon FLR. However, the factors defining establishment success within Brazil nut restoration activities remain unknown. 2. Here, we evaluate the effect of management practices, restoration site (pastures, agroforestry, secondary forest and canopy gaps in old growth forest) and environmental conditions on the establishment success (tree growth, survival and fruit production) of Brazil nut restoration projects implemented by smallholders in the Peruvian Amazon. We performed a field study at 25 restoration sites of 1–38 years in age, where we conducted measurements on 481 trees and interviewed 21 smallholders. We used mixed effect models to identify drivers of performance. 3. Twenty years after planting, diameter growth in secondary forests was 38%, 34%, and 24% higher than in canopy gaps, pastures, and agroforestry sites, respectively. Survival rate was similar for trees planted in pastures and secondary forests, but 15–20% higher there than trees planted in agroforestry sites, and 7–12% higher than in canopy gaps. Fruit production was 262% higher for reproductive trees in secondary forest sites compared to pastures, but production probability did not differ between restoration sites. These results show that secondary forests are the most suitable sites for planting Brazil nut trees. 4. In addition to restoration site effects, we also found significant effects of management practices. Survival rate increased with application of fire for clearing and weeding and economic investments and decreased with potentially inefficient herbivore protection. Fruit production was lower for trees planted further away from smallholders’ homes. These results show that smallholders’ management has a substantial effect on establishment success. 5. Our findings suggest a significant importance of post-planting maintenance of trees to increase success of FLR projects. Further, our study shows that evaluation of past restoration activities can guide future forest restoration in tropical landscapes.